2008
DOI: 10.1002/aur.38
|View full text |Cite
|
Sign up to set email alerts
|

Do children with autism spectrum disorders show a shape bias in word learning?

Abstract: Many children with autism spectrum disorders (ASD) acquire a sizeable lexicon. However, these children also seem to understand and/or store the meanings of words differently from typically developing children. One of the mechanisms that helps typically developing children learn novel words is the shape bias, in which the referent of a noun is mapped onto the shape of an object, rather than onto its color, texture, or size. We hypothesized that children with Autistic Disorder would show reduced or absent shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
166
4
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(185 citation statements)
references
References 39 publications
12
166
4
3
Order By: Relevance
“…In contrast to Swenson et al (2007), Tek, Jaffery, Fein and Naigles (2008) found differences between fourteen children with ASD (aged 2;2 to 3;1) and fifteen typically developing language-matched children (1;6 to 1;11) when intermodal preferential looking was measured during four visits over twelve months. The two groups did not differ in noun bias, consistent with Swenson et al (2007), but they did differ in their tendency to show a shape bias (i.e.…”
Section: Lexical Development In Typically Developing Childrencontrasting
confidence: 62%
See 1 more Smart Citation
“…In contrast to Swenson et al (2007), Tek, Jaffery, Fein and Naigles (2008) found differences between fourteen children with ASD (aged 2;2 to 3;1) and fifteen typically developing language-matched children (1;6 to 1;11) when intermodal preferential looking was measured during four visits over twelve months. The two groups did not differ in noun bias, consistent with Swenson et al (2007), but they did differ in their tendency to show a shape bias (i.e.…”
Section: Lexical Development In Typically Developing Childrencontrasting
confidence: 62%
“…The literature on lexical development in children with ASD raises the same issue. The 'delay' view is supported by the ways lexical development in children with ASD resembles typical lexical development, namely that children with ASD (a) tend to acquire more words in their lexicons as they get older (Charman et al, 2003 ;Smith et al, 2007) ; (b) vary widely in lexicon size (Charman et al, 2003 ;Ellis Weismer et al, 2010 ;Ellis Weismer et al, 2011 ;Luyster et al, 2007 ;Luyster et al, 2008); (c) show a predominance of nouns and roughly the same percentages of nouns, verbs and closed-class terms as typically developing children with similar vocabulary sizes (Charman et al, 2003); (d) exhibit a noun bias in laboratory preferential looking studies (Swenson et al, 2007 ;Tek et al, 2008) ; and (e) manifest high correlations between parent-reported vocabulary scores and directly administered expressive language tests (Ellis Weismer et al, 2010 ;Luyster et al, 2008). On the other hand, the 'deviance ' view is supported by the ways in which lexical development in children with ASD differs from typical development, such as (a) a much higher percentage of severe vocabulary delays (Charman et al, 2003, Ellis Weismer et al, 2011Luyster et al, 2007 ;Luyster et al, 2008) ; (b) much greater variation in rate of vocabulary growth over time (Smith et al, 2007) ; (c) weaker associations between lexicon size and grammatical complexity than late talkers with the same-size lexicons (Ellis Weismer et al, 2011) ; failure to show a shape bias on novel word tasks (Tek et al, 2008).…”
Section: Lexical Development In Typically Developing Childrenmentioning
confidence: 99%
“…), prior to showing the shape bias. Indeed, this early noun vocabulary facilitates shape bias understanding (Samuelson 2002;Smith et al 2002;Tek et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bartolucci et al 1976;Eigsti and Bennetto 2009;Howlin 1984;Mitchell et al 2006;Van Meter et al 1997). A delay account would predict that children with ASD may eventually learn to use the shape bias heuristic, but not until they have more experience with objects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although subsequent research has shown that children aged around 4 or 5 (Nilsen & Graham, 2009), 5 or 6 (Bahtiyar & Küntay, 2008;Nadig & Sedivy, 2002) show sensitivity to the addressee's perspective in the production of contrastive adjectives, research has also shown that unlike adults, AUDIENCE DESIGN IN CHILDREN 6 words to novel referents like children without ASD (Tek, Jaffery, Fein, & Naigles, 2008) and use the same contextual information as their controls when doing so (De Marchena, Eigsti, Worek, Ono, & Snedeker, 2011;Preissler & Carey, 2005). When producing sentences, high-functioning children with ASD can also align sentence structures with their partner, demonstrating unimpaired syntactic representations (Allen, Haywood, Rajendran, & Branigan, 2010).…”
Section: Introductionmentioning
confidence: 99%